Effect of microtrichia on the interlocking mechanism in the Asian ladybeetle, Harmonia axyridis (Coleoptera: Coccinellidae) - Sun, Jiyu; Liu, Chao; Bhushan, Bharat; Wu, Wei; Tong, Jin (Beilstein Journal of Nanotechnology, 2018)
The hindwings of beetles are folded under the elytra when they are at rest but are extended during flight, which can provide bioinspiration for the design of deployable micro air vehicles (MAVs). Beetle hindwings must be able to be both securely locked under the elytra and freely extended for flight, depending on the required action. To investigate the locking mechanism, this study used environmental scanning electron microscopy (ESEM) to examine the microstructures of the elytra, hindwings and abdomen of the Asian ladybeetle, Harmonia axyridis (Pallas, 1773). On the ventral side (VS) of the elytra, the microtrichia show a transitional structure from the lateral edge to the medial edge. On the hindwing surface, the folded regions were observed on both the dorsal side (DS) and the VS. On the abdomen, the microtrichia between the abdominal segments show a cyclical change from sparse to dense in each segment in the middle of the abdomen. Furthermore, the different directions of microtrichia that lead to self-locking friction on the surfaces of the hindwing, elytron and abdomen appear to facilitate interlocking. A model for the interlocking of the hindwings of the H. axyridis was established, and its underlying mechanism is discussed.
Keywords: anti-wetting; folding process; interlocking mechanism; micro air vehicles; microtrichia

5th International and 41st National Conference on Fluid Mechanics and Fluid Power - Huda, N.; Anwer, S. F. (The effects of leading edge orientation on the aerodynamic performance of dragon fly wing section in gliding flight, Kanpur, India, 12.12.2014-14.12.2014, 2017)

Proceedings of the ASME 2015 International Design Engineering Technical Conferences and Computers and Information in Engineering Conference - Saito, K.; Okabe, Y. (Elastic Wing Deployments in Beetles and Their Folding Mechanisms, Boston, MA, U.S.A., 2.8.2015-5.8.2015)

(untitled) - Hammond, P. M. (Biol. J. Linn. Soc., 1985)

(untitled) - Gorb, S. N. (Am. Zool., 2001)

Carabid Beetles - Hammond, P. M. (Wing-folding Mechanisms of Beetles, with Special Reference to Investigations of Adephagan Phylogeny (Coleoptera), 1979)

Abstract Papers II. Biomechanic Workshop of the studygroup morphology - Karner, M. (Bifunctional muscles and interlocking mechanism in cantharis: How not to move the wings, 1997)

(untitled) - Kukalová-Peck, J. (Can. J. Zool., 1983)

(untitled) - Frantsevich, L. (J. Exp. Biol., 2010)

(untitled) - Sun, J.; Ling, M.; Wu, W.; Bhushan, B.; Tong, J. (Int. J. Mol. Sci., 2014)

(untitled) - Haas, F.; Gorb, S.; Blickhan, R. (Proc. R. Soc. London, Ser. B, 2000)

(untitled) - Michels, J.; Appel, E.; Gorb, S. N. (Beilstein J. Nanotechnol., 2016)

(untitled) - Hass, F.; Beutel, R. G. (Zoology (Munich, Ger.), 2001)

Evolution of the Beetle Hind Wing, With Special Reference to Folding (Insecta, Coleoptera) - Fedorenko, D. N. (Pensoft, 2009)

(untitled) - Saito, K.; Nomura, S.; Yamamoto, S.; Niyama, R.; Okabe, Y. (Proc. Natl. Acad. Sci. U. S. A., 2017)

(untitled) - Frantsevich, L. (Zoology (Munich, Ger.), 2012)

(untitled) - Frantsevich, L.; Dai, Z.; Wang, W. Y.; Zhang, Y. (J. Exp. Biol., 2005)

(untitled) - Gorb, S. N. (Int. J. Insect Morphol. Embryol., 1998)

Proceedings of the Third International Symposium on the Chrysomelidae - Samuelson, G. A. (An elytron to body meshing mechanism of possible significance in the higher classification of Chrysomelidae (Coleoptera), 1994)

Chrysomelidae Biology: The Classification, Phylogeny and Genetics - Samuelson, G. A. (Binding sites: Elytron-to-body meshing structures of possible significance in the higher classification of Chrysomeloidea, 1996)

(untitled) - Burks, R. A.; Heraty, J. M. (Arthropod Struct. Dev., 2015)

(untitled) - Qian, J.; Chi, D.; Chai, R. (J. For. Res. (Harbin, China), 2016)

(untitled) - Xiang, J.; Du, J.; Li, D.; Zhen, C. (Microsc. Res. Tech., 2016)

The Insects Structure and Function - Chapman, R. F. (English Universities Press, 1998)

(untitled) - Frantsevich, L. (J. Insect Physiol., 2012)

(untitled) - Hu, H.-M.; Watson, J. A.; Cribb, B. W.; Watson, G. S. (Biofouling, 2011)

(untitled) - Linghu, Z.; Zhao, C.; Yang, H.; Zheng, X. (Sci. Bull., 2015)

(untitled) - Hu, H.-M.; Watson, G. S.; Cribb, B. W.; Watson, J. A. (J. Exp. Biol., 2011)

(untitled) - Fedorenko, D. N. (Biol. Bull. Rev., 2015)

(untitled) - Aideo, S. N.; Mohanta, D. (Appl. Surf. Sci., 2016)

(untitled) - Sun, T.; Feng, L.; Gao, X.; Jiang, L. (Acc. Chem. Res., 2005)

(untitled) - Gorb, S. N.; Kesel, A.; Berger, J. (Arthropod Struct. Dev., 2000)

(untitled) - Gao, X.; Jiang, L. (Nature, 2004)

(untitled) - Sun, M.; Watson, G. S.; Zheng, Y.; Watson, J. A.; Liang, A. (J. Exp. Biol., 2009)

(untitled) - Watson, G. S.; Cribb, B. W.; Watson, J. A. (J. Struct. Biol., 2010)

(untitled) - Krishnan, K. G.; Milionis, A.; Loth, E.; Farrell, T. E.; Crouch, J. D.; Berry, D. H. (Appl. Surf. Sci., 2017)

(untitled) - Bormashenko, E.; Bormashenko, Y.; Stein, T.; Whyman, G.; Bormashenko, E. (J. Colloid Interface Sci., 2007)

Encyclopedia of Insects - Resh, V. H.; Cardé, R. T. (Elsevier, 2003)

(untitled) - Murphy, J. T.; Hu, H. (Exp. Fluids, 2010)

Wing Folding in Beetles - Brackenbury, J. H. (Kluwer Academic Publishers, 1998)